Conclusion: Patterns of Non-Territorial Autonomy. Issue 1 (1st January 2016) - Coakley, John
Abstract: This article seeks to generalise about the significance of non-territorial autonomy as a mechanism for the management of ethnic conflict on the basis of a set of case studies covering the Ottoman empire and its successor states, the Habsburg monarchy, the Jewish minorities of Europe, interwar Estonia, contemporary Belgium, and two indigenous peoples, the Sámi in Norway and Maori in New Zealand. It begins by assessing the extent to which the spatial distribution of ethnonational communities determined the range of autonomy options available—whether these might be territorial or whether only non-territorial autonomy would be realistic. The article continues with an assessment of the significance of 'autonomy' in circumstances where the institutions with which it is associated enjoy a non-territorial rather than a territorial writ. It concludes by suggesting that in almost all cases where autonomy is extended to a minority within a state this is exercised on a territorial basis, and that in many cases of non-territorial autonomy, or national–cultural autonomy, the powers assumed by the 'autonomous' institutions are substantially symbolic. It argues that notwithstanding the limited empirical evidence for the existence of non-territorial autonomy, this device should not be written off at a normative level.